The charm school - DeMille, Nelson (New York : Warner Books, 1988)
A young American tourist stumbles onto a giant Soviet secret--a school for KGB agents that uses MIA/POWs from Vietnam as instructors. The American embassy becomes involved when, in a panic, the tourist calls them and then disappears.
National College of Business and Arts
Keywords: Soviet Union -- Fiction; Detective and mystery fiction